Connexin hemichannels in the lens - Beyer, Eric C.; Berthoud, Viviana M. (Frontiers in Physiology, 2014)
The normal function and survival of cells in the avascular lens is facilitated by intercellular communication through an extensive network of gap junctions formed predominantly by three connexins (Cx43, Cx46, and Cx50). In expression systems, these connexins can all induce hemi-channel currents, but other lens proteins (e.g., pannexin1) can also induce similar currents. Hemichannel currents have been detected in isolated lens fiber cells. These hemichannels may make significant contributions to normal lens physiology and pathophysiology. Studies of some connexin mutants linked to congenital cataracts have implicated hemichannels with aberrant voltage-dependent gating or modulation by divalent cations in disease pathogenesis. Hemichannels may also contribute to age- and disease-related cataracts.